Process behaviour in a packed absorption column for high pressure CO2 absorption from natural gas using PZ + AMP blended solution - Hairul, N.A.H. (Elsevier B.V., 2017)
This paper reports the use of piperazine promoted 2-amino-2-methyl-1-propanol (PZ + AMP) blended solution for the removal of high concentration CO2 in natural gas (NG). The process behaviour was investigated by conducting the experiments in a bench-scale packed absorption column at high pressure conditions. The CO2 concentration and temperature profiles along the column were presented in order to study the process behaviour in the column at various operating pressures, CO2 concentration in NG, total gas flow rates, liquid flow rates, amine concentration and inlet liquid temperature. The temperature bulge was observed in the column and further discussed in this paper. © 2016